Acute Abdomen Secondary to Incarcerated Umbilical Hernia after Treatment of Massive Cirrhotic Ascites - Hiang Keat Tan; Pik Eu Chang (Case Reports in Hepatology)
Umbilical herniation is common in patients with liver cirrhosis and ascites. Rarely, they suffer from incarceration and strangulation of the umbilical hernia after treatment of ascites. We report 3 cases of umbilical hernia incarceration following removal of massive ascites with different treatment modalities. Physicians managing this group of patients should be aware of this rare and potentially fatal complication.